KAJIAN KUALITAS GAS CO DAN NO2 DI TEMPAT PARKIR LOWER GROUND DAN BASEMENT MARVELL CITY MALL SURABAYA (STUDI KASUS TAHUN 2019) - Naniek Ratni JAR; Retno Patmasari (EnviroUS, 2022)
More and more mall building constructions, the land needed for needs such as parking also needs to be considered in its construction. Especially the construction in the basement (basement). The analytical method used for CO and NO2 gas is Electrochemical Sensor with a Gas Analyzer. The measurement results of the two polluting gases, namely CO and NO2, are compared with the Quality Standards PER.13/MEN/X/2011 PER.13/MEN/X/2011 for CO gas standard is 25 ppm, while for NO2 gas standard is 3 ppm. So, it's still safe to be in the room, which means it's still safe. There are significant and significant average differences CO and NO2 levels on the Lower Ground floor were compared to the basement with a p-value of 0.000. The results of the statistical test of the Pearson- correlation method show a positive correlation between temperature and CO and NO2, a negative correlation between humidity and CO and NO2.